2021
DOI: 10.3390/ijms222312909
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incorporation of Different dn-Electron Metal Cations into Biologically Active System on Its Biological and Physicochemical Properties

Abstract: Three new compounds, namely [HL]2+[CuCl4]2−, [HL]2+[ZnCl4]2−, and [HL]2+[CdCl4]2− (where L: imipramine) were synthesized and their physicochemical and biological properties were thoroughly investigated. All three compounds form isostructural, crystalline systems, which have been studied using Single-Crystal X-ray diffraction analysis (SC-XRD) and Fourier-transform infrared spectroscopy (FTIR). The thermal stability was investigated using thermogravimetric analysis (TGA) and melting points for all compounds hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This issue arises when IMI and Zn are administered as separate oral treatments in animal and human experiments. Therefore, Rogalewicz et al [ 72 ] developed a methodology for obtaining and synthesizing an IMI-Zn complex compound, whose antidepressant activity in the FST in mice was assessed in these studies. The outcomes of the conducted investigation revealed that the IMI-Zn complex displayed an antidepressant-like effect that varied with dosage.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This issue arises when IMI and Zn are administered as separate oral treatments in animal and human experiments. Therefore, Rogalewicz et al [ 72 ] developed a methodology for obtaining and synthesizing an IMI-Zn complex compound, whose antidepressant activity in the FST in mice was assessed in these studies. The outcomes of the conducted investigation revealed that the IMI-Zn complex displayed an antidepressant-like effect that varied with dosage.…”
Section: Discussionmentioning
confidence: 99%
“…In the acute toxicity studies conducted using the Zebrafish model, the IMI-Zn complex compound was found to have no adverse effects on fish development. Additionally, it exhibited a dose-dependent impact on the spontaneous locomotor activity of 5-day-old larvae—higher doses of the IMI-Zn complex inhibited locomotor activity, while lower doses increased it [ 72 ]. Additionally, Rogalewicz et al [ 72 ] demonstrated that the IMI-Zn complex, specifically at a concentration of 3 μM, produced a similar anxiolytic-like effect in a light/dark test compared to diazepam, a commonly used anxiolytic drug.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations